2012
DOI: 10.1515/cclm-2012-0201
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of POC lactate methods for fetal and perinatal lactate testing: considerations for accuracy, specificity and decision making criteria

Abstract: The three electrochemical POC devices can measure fetal lactate reliably. StatStrip Lactate showed a closer correlation and concordance to our laboratory reference method. The results of this study indicate the requirement for predetermining the reliability of POC lactate methods before use present in fetal and perinatal settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…The correlation and categorization of BLAC from both testing methods show that POCT can accurately measure blood lactic acid values in cancer patients. This finding is consistent with those from previous studies that have shown that a POC device can provide reliable blood lactic acid measurements in ED and delivery rooms [8][9][10]. The assessment of lactic acid by POCT in cancer patients can timely identify who is at risk for sepsis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation and categorization of BLAC from both testing methods show that POCT can accurately measure blood lactic acid values in cancer patients. This finding is consistent with those from previous studies that have shown that a POC device can provide reliable blood lactic acid measurements in ED and delivery rooms [8][9][10]. The assessment of lactic acid by POCT in cancer patients can timely identify who is at risk for sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that POC devices are able provide reliable measurements of lactate levels in delivery rooms and emergency departments (ED) [8][9][10]. In the study reported here, we shift the focus to cancer patients who not only have cells producing more lactate but may be receiving treatment making them more susceptible to systemic infections.…”
Section: Introductionmentioning
confidence: 98%
“…Frequently evaluated lactate POCT devices are strip-analyzers, like the Lactate-Pro (Arkray) and StatStrip Lactate (Nova Biomedical), which have been shown to have satisfactory analytical performance. The StatStrip Lactate was found to perform the best, based on interference studies and imprecision (coefficient of variation, CV) measurements [11] , [12] . Recently, these conclusions were confirmed in a large study population resulting in a strong reduction in failure rates, compared with fetal scalp blood sampling, mainly caused by a shortage of sample resulting in no measurement on blood gas analyzers [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [23][24][25][26] have shown promising results. However, some of the previous studies were undertaken in circumstances that did not adequately represent real labor ward conditions for analyzing fetal scalp blood samples.…”
Section: Discussionmentioning
confidence: 98%